المسؤولية الجنائية تجاه المال العام دراسة مقارنة بين الفقه الإسلامي والقانون الجزائري - جموعي, شطم; شعيب, زلاسي (جامعة الوادي university of eloued, 2023)
تتناول هذه الدراسة المسؤوليّة الجنائيّة اتجاه المال العام في مختلف أشكاله من خلال إجراء ''دراسة مقارنة'' بين الفقه الإسلامي، والقانون الجزائري، وهو موضوع بالغ الأهمية إذا وضعنا في الاعتبار أنّ المال العام هو حق عام للمجتمع، وكذا حق واجب الحفظ للأجيال اللاحقة، وإذ تسعى مختلف المجتمعات لتنظيم تسيير المال العام، من خلال سن القوانين المنظمة لتسيير المال العام، وكذا استحداث الآليات الرقابيّة للموظف المكلف بحفظ المال العام، وقد توصلت الدّراسة إلى أن نصوص القانون الجزائري متوافقة مع أحكام الفقه الاسلامي في تأمين حماية المال العام، مع اختلاف آراء الفقهاء مع رجال القانون في حال التعدّي على المال العام، والعقوبات المسلطة على المعتدي بين الفقه الإسلامي والقانون الجزائري، وخلصت الدّراسة إلى مجموعة من النتائج، من أبرزها فهم المشرّع الجزائري مقصد الشريعة من إيقاع الحدود، وسعيه لتنفيذها وفقا لأركانها وشروطها في المحاكم المدنية، وفق ما جاءت به نصوص الشّريعة الإسلامية، وكذا بعض التوصيات كتنظيم عمل الإدارة، وفق آليات وطرق تغلق المجال على من تسول له نفسه التّعدّي على الأموال، وتحسيسهم في ذات الوقت بمسؤوليّهم عن حفظ المال العام، الذي هو من الأمانة الواجب حفظها.This study deals with criminal liability towards public money in its various forms by conducting a “comparative study” between Islamic jurisprudence and Algerian law, which is a very important topic if we take into account that public money is a general right of society, as well as a right that must be preserved for subsequent generations. As various societies seek to regulate the management of public money, through the enactment of laws regulating the management of public money, as well as the creation of oversight mechanisms for the employee charged with preserving public money, the study concluded that the texts of Algerian law are compatible with the provisions of Islamic jurisprudence in ensuring the protection of public money, with differing opinions. The jurists are with the jurists in the event of infringement on public funds, and the penalties imposed on the aggressor between Islamic jurisprudence and Algerian law. The study concluded with a set of results, the most prominent of which is the Algerian legislator’s understanding of the purpose of Sharia law in imposing punishments, and his endeavor to implement them according to its pillars and conditions in the civil courts, according to what It was brought by the texts of Islamic Sharia, as well as some recommendations, such as organizing the work of the administration, according to mechanisms and methods that close the scope to those who dare to encroach on funds, and at the same time make them aware of their responsibility for preserving public money, which is a trust that must be preserved.
مذكرة
Keywords: المسؤولية الجنائية، المال العام، الموظف العام، الوظيفة العامة، الجرائم ضد الأموال، الفقه الإسلامي، التشريع الجزائري، قانون العقوبات.; criminal responsibility, public money, public servant, public office, crimes against money, Islamic jurisprudence, Algerian legislation, penal code.